Efektivitas Pendekatan Fisioterapi Dalam Mengelola Nyeri Punggung Bawah Dengan Intervensi Elektroterapi dan Exercise Dalam Mengurangi Nyeri - Ismaningsih Ismaningsih; Ade Saputra; Nurmaliza Nurmaliza (LPPM STIKES Siti Hajar dan Insight Power, 2023)
This study aims to determine the effectiveness of the physhiotherapy approach using electrotherapy (TENS) and exercise in reducing pain in patients wits low back pain. Low back pain is defined as pain in the posterior region of the lower back. The border of the lower back is in the area of the fifth lumbar and saclar vertebrae (L5-S1). The pain usually accompanied by radiating to the legs and feet, and only 15% of these have been diagnosed as having an underlying cause. certain. This study used pre and post experimental methods with a simple of 10 people, and evaluation measurements were carried out using VAS. In this treatment group using the normality test using the Shapirowilk test on all pre-test and post-test variable, p value >0.05 which means P>0.05 then the results of the hypothesis using the paired samples t_test test in this study obtained a value of P = 0.000 (P>0.05) with a mean value of .900±1.286 which means that electrotherapy and exercise intervention are significant in reducing pain in LBP. Keywords: Low Back Pain, Elektroterapi, Exercise